A Heterogenous Agents Model Usable for the Analysis of Currency Transaction Taxes - Markus Demary (Kiel University, Department of Economics, 2007)
We extend the model by DeGrauwe and Grimaldi (2006, EER) by currency transaction taxes. This model explains the exchange rate behavior by the interaction of heterogeneous traders who display either trend chasing behavior or rely on a return of the exchange rate back to its arbitrage free fundamental value. Within this model framework we can show analytically that the steady-state of the original model is unaffected by the transaction tax rate. We inferred from numerical simulations that the transaction tax is able to reduce the number of speculative equilibria to zero. Moreover, we show that the tax will lead to a faster convergence of the system back to its fundamental steady state.
Keywords: G15; F32; F31; G18; C15; 330; Currency Transaction Taxes; Exchange Rates; Financial Market Volatility; Heterogenous Agents Model; Numerical Simulation; Wechselkurs; Devisenhandel; Agent-based Model; Rationale Erwartung; Effizienzmarktthese; Transaktionskosten; Tobinsteuer; Devisenspekulation; Theorie